A centralidade de Mamanguape(PB) e sua relação com as cidades pequenas do litoral norte paraibano - Soares de Farias, Raquel (2013)
This study aimed to analyze the centrality exerted by the city of Mamanguape in the microregion of North Coast, under the perspective of teaching higher education. To this end, we seek, in the course of research elaboration, to reflect on the relationships between Mamanguape and other cities of the North Coast microregion; to understand the centrality of Mamanguape (PB) in different historical periods and to investigate the major changes occurred in urban space of the city after the UFPB Campus IV implementation. Despite the intense influences of metropolis over other cities belonging to a given region, currently it is noticeable the emergence of new centers of centrality that are not necessarily cities of medium and large size and this comes instigating many researchers to focus their studies for these regions. Mamanguape, for example, even classified as a small town has always presented a dynamic and significant centrality, what makes the other cities of the the North Coast microregion have a close relationship with it. Based on these objectives and context, this work was structured in three chapters and it was necessary to survey the theoretical and methodological sources on the city, centrality, as well as of reflections for investigation of small towns. For this, To this end, our analysis came from the theoretical and conceptual underpinnings of small towns and centrality presented by Maia (2009), Fresca (2010), Santos (1979), Corrêa (1999, 2004), Lefebvre (1999), Villaça (2009) and Spósito (1998). The research allowed us to state that the arrival of the Campus IV in Mamanguape intensified its centrality in the microregion. It was identified that the majority of students are coming from the municipalities of the North Coast which narrowed their relationship with them, because lot of people started to circulate in the city to seek higher education which resulted in the change / heating of other sectors that are not necessarily connected to the university.